Luxembourgite, AgCuPbBi4Se8, a new mineral species from Bivels, Grand Duchy of Luxembourg - S. Philippo; F. Hatert; Y. Bruni; P. Vignola; J. Sejkora (European Journal of Mineralogy, 2020)
Luxembourgite, ideally AgCuPbBi4Se8, is a new selenide discovered at Bivels, Grand Duchy of Luxembourg. The mineral forms tiny fibres reaching 200 µm in length and 5 µm in diameter, which are deposited on dolomite crystals. Luxembourgite is grey, with a metallic lustre and without cleavage planes; its Mohs hardness is 3 and its calculated density is 8.00 g cm−3. Electron-microprobe analyses indicate an empirical formula Ag1.00(Cu0.82Ag0.20Fe0.01)Σ1.03Pb1.13Bi4.11(Se7.72S0.01)Σ7.73, calculated on the basis of 15 atoms per formula unit. A single-crystal structure refinement was performed to R1=0.0476, in the P21∕m space group, with a=13.002(1), b=4.1543(3), c=15.312(2) Å, β=108.92(1)∘<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="73pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="4d920107eb4a98473050fd7bdaf16dee"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-32-449-2020-ie00001.svg" width="73pt" height="13pt" src="ejm-32-449-2020-ie00001.png"/></svg:svg>, V=782.4(2) Å3, Z=2. The crystal structure is similar to that of litochlebite and watkinsonite and can be described as an alternation of two types of anionic layers: a pseudotetragonal layer four atoms thick and a pseudohexagonal layer that is one atom thick. In the pseudotetragonal layers the Bi1, Bi2 ,Bi3, Pb, and Ag1 atoms are localised, while the Cu2 and Bi4 atoms occur between the pseudotetragonal and the pseudohexagonal layers. Bi1, Bi2, and Bi3 atoms occur in weakly distorted octahedral sites, whereas Bi4 occurs in a distorted 7-coordinated site. Ag1 occupies a fairly regular octahedral site, Cu2 a tetrahedral position, and Pb occurs on a very distorted 8-coordinated site.